Hyperfocus symptom and internet addiction in individuals with attention-deficit/hyperactivity disorder trait - Ishii, Sayuri; Takagi, Shunsuke; Kobayashi, Nanase; Jitoku, Daisuke; Sugihara, Genichi; Takahashi, Hidehiko (Frontiers in Psychiatry, 2023)
Background: Hyperfocus symptom is the intense concentration on a certain object. It is a common but often overlooked symptom in those with attention-deficit/hyperactivity disorder (ADHD). Hyperfocus can be related to behavioral addictions such as internet addiction (IA), because it disrupts attention control and results in a focus on inappropriate behaviors. However, no studies have examined the relationship between hyperfocus symptom and IA in relation to ADHD. This study investigated the status of IA and hyperfocus, the mediation effect of hyperfocus in relation to IA, and the relationship between ADHD subtypes and hyperfocus in those with ADHD symptoms. Methods: This web-based cross-sectional study included 3,500 Japanese adults who completed internet-based questionnaires, which included the Adult ADHD Self-Report Scale (ASRS), Internet Addiction Test (IAT), and Hyperfocus Scale (HFS) to assess ADHD symptoms, internet dependence, and hyperfocus symptoms, respectively. The mediating role of HFS in the relationship between ASRS and IAT was assessed by mediation analysis. To analyze the relationship between hyperfocus symptoms and ADHD subtypes, we compared the correlation of HFS with the Inattention and Hyperactive Scores of ASRS. Results: ADHD traits were associated with higher IAT scores (p < 0.001) and higher HFS scores (p < 0.001). Mediation analysis and bootstrap testing showed that HFS significantly mediated the association between ASRS and IAT. Analyses of ADHD subtypes demonstrated that HFS was significantly correlated with the Inattention (R = 0.597, p < 0.001) and Hyperactive (R = 0.523, p < 0.001) Scores. The correlation between HFS and the Inattention Score was significantly higher than that between HFS and the Hyperactive Score (p < 0.001). Conclusion: Our findings suggest that hyperfocus may play an important role in addictive behavior in ADHD as a manifestation of attentional control malfunction.